What are the impact and the optimal design of a physical prehabilitation program in patients with esophagogastric cancer awaiting surgery? A systematic review - Elise Piraux; Gregory Reychler; Louise Maertens de Noordhout; Patrice Forget; Yannick Deswysen; Gilles Caty (BMC, 2021)
Abstract Background Substantial postoperative complications occur after tumor resection for esophagogastric cancers. Physical prehabilitation programs aim to prepare patients for surgery by improving their functional status with the aim of reducing postoperative complications. This systematic review aims to summarize the effects of physical prehabilitation programs on exercise capacity, muscle strength, respiratory muscle function, postoperative outcomes, and health-related quality of life and to determine the optimal design of such a program to improve these outcomes in esophagogastric cancer patients undergoing tumor resection. Methods A systematic literature review was conducted using PubMed, The Cochrane Library, Scopus, and PEDro databases to identify studies evaluating the effects of physical prehabilitation program on exercise capacity, muscle strength, respiratory muscle function, postoperative complications, length of hospital stay, mortality, and health-related quality of life in patients with esophagogastric cancer awaiting surgery. Data from all studies meeting the inclusion criteria were extracted. The quality of each selected study was determined using the Downs and Black checklist. Results Seven studies with 645 participants were included. The preoperative exercise program consisted of respiratory training alone in three studies, a combination of aerobic and resistance training in two studies, and a combination of respiratory, aerobic, and resistance training in two studies. Training frequency ranged from three times a day to twice a week and each session lasted between 20 and 75 min. Four studies were of fair quality and three of good quality. Some studies reported improvements in maximal inspiratory pressure, inspiratory muscle endurance, postoperative (pulmonary) complications, and length of hospital stay in the preoperative exercise group compared to the control group. Conclusion This systematic review reports the current evidence for physical prehabilitation programs in patients with esophagogastric cancer awaiting surgery. However, due to the limited number of randomized controlled trials, the significant heterogeneity of exercise programs, and the questionable quality of the studies, higher quality randomized controlled trials are needed. Trial registration PROSPERO Registration Number: CRD42020176353 .